Symptom Clustering and Syndromic Knowledge in Diagnostic Problem Solving - Wu, Thomas D. (1989)
The diagnostic solution of complex, multidisorder cases requires a different approach from the standard paradigm of triggering hypotheses and scoring them. We investigate an alternative method that introduces an intermediate step of structuring the evidence. This method, called symptom clustering, emphasizes the attribution of diseases to symptoms, as represented by attributional models. The clinical analogue of the symptom clustering method is syndromic knowledge. The heuristic power of syndromes may be exploited to guide search for the correct attributional model. Syndromic knowledge and symptom clustering are analogues because both express propositions about common causality among symptoms.